A new generalized similarity measure based on intuitionistic trapezoidal fuzzy multi-numbers: Turkey's sustainable tourism economy strategy application - Vakkas Uluçay; Nuh Okumuş (Journal of Fuzzy Extension and Applications)
Sustainable tourism is one of today's rapidly growing economic areas. Promotional activities should be carried out to increase the income from sustainable tourism. To carry out these studies effectively, it is necessary to choose the best centre. Multi-Criteria Decision-Making (MCDM) approaches can be used to select the best tourism centre. In this paper, a new generalized similarity measure on intuitionistic trapezoidal fuzzy multi-numbers is developed for decision information. The desirable properties of this proposed measure are presented in detail. Further, we develop an approach to the MCDM problem based on the proposed measure. Finally, the effectiveness and applicability of our proposed MCDM model, as well as comparison analysis with other methods, are illustrated with a practical example.